Changing Trends in oral cancer – a global scenario (Nepal Journal of Epidemiology, 2017)
Oral cancer is one of the highly prevalent cancers worldwide and a leading cause of mortality in certain regions like South-Central Asia. It is a major public health problem. Late diagnosis, high mortality rates and morbidity are characteristics of the disease worldwide. For control of oral cancer an idea of the coverage of the same in the various regions is necessary. The estimated incidence, mortality and 5-year survival due to lip, oral cavity cancer in world is 3, 00, 373(2.1%), 1, 45, 328(1.8%) and 7, 02, 149(2.2%) respectively according to data of GLOBOCAN 2012. A changing trend in incidence and prevalence of oral cancer has been observed with more women and youngsters being affected by oral cancer.